Influence of soil chemical and physical properties on occurrence of Trichoderma spp. in Embu, Kenya = Influencia de las propiedades químicas y físicas del suelo sobre la ocurrencia de Trichoderma spp. en Embu, Kenia - Okoth, Sheila A.; Okoth, Peter F.; Muya, EA (2009)
Soil samples were collected from 8 land use types in Embu to study the effects of land use on soil chemical and physical parameters and on the occurrence of Trichoderma spp. The fungus was recovered from the soil using the dilution plate and soil washing technique. The remaining soil samples were used to measure the following characters of the soil; pH was determined in 1:1 (w/v) soil – water suspension with pH meter, total nitrogen was determined by the Kjeldahl method, available nutrients P, K, Na, Ca and Mg were determined using Mehlich method while total organic carbon was determined by calorimetric method. Land use type (LUT), plant cover, and soil physical and chemical properties influenced Trichoderma occurrence. The frequency of isolation of Trichoderma spp. was highest in napier LUT followed by indigenous forests. Carbon, N, Mg and Fe loaded with forest land use type suggesting their influence on fungal diversity in this LUT. The forests had clay loam soils with higher porosity and water retention capacity compared with the cultivated LUTs which were characterized with clay soils and bulk density. Napier together with other cultivated LUTs which had low records of the fungus loaded positively with Mn and Cu. This implied that plant type was the major determining factor for the high population of Trichoderma recorded in napier LUT. The diversity of soil factors observed in the fallow lands explained the influence of land management on soil physical and chemical characteristics which in turn determined the fungal distribution. Soil depth (0-20cm) did not influence soil factors though fungal diversity, abundance and evenness varied with depth suggesting the influence of other drivers.This study explains the fact that many factors interact in determining the occurrence of Trichoderma spp. and that in some situations it is the soil that is the key factor determining fungal occurrence and diversity while in others it is the plant type.